2022
DOI: 10.3390/medicina58040538
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hip Center Position and Isokinetic Hip Muscle Performance after Anterolateral Muscle-Sparing Total Hip Arthroplasty

Abstract: Background and objectives: The superior placement of the acetabular cup induced the delayed recovery of abductor muscle moment after total hip arthroplasty (THA) with a conventional posterior approach. The anterior-based muscle-sparing (ABMS) THA effectively reduces soft tissue damage, including muscles. The influence of hip center position on anterior-based muscle-sparing (ABMS) total hip arthroplasty (THA) for post-operative hip muscle strength was unclear. We evaluate whether the hip center position affects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Additionally, the superior placement of the hip center caused delayed recovery of abductor muscle strength in hips with anterolateral minimally invasive THA. There seems to exist no biomechanical reason why the same should not also be the case for the muscle-sparing approach [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the superior placement of the hip center caused delayed recovery of abductor muscle strength in hips with anterolateral minimally invasive THA. There seems to exist no biomechanical reason why the same should not also be the case for the muscle-sparing approach [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the superior placement of the hip center caused delayed recovery of abductor muscle strength in hips with anterolateral minimally invasive THA. There seems to exist no biomechanical reason why the same should not also be the case for the muscle-sparing approach [17,18]. Many research papers focus on medialization of the COR, sometimes linked with the increase in femoral offset, although the correlation between the offset and the range of motion is also under discussion [19].…”
Section: Cor -Center Of Rotationmentioning
confidence: 99%
“…Tanaka et al studied the influence of hip center position on abductor muscular strength with a Biodex system. They detected an association between superior placement and delayed recovery of abductor muscular strength [28]. Although total hip arthroplasty (THA) is expected to result in a postoperative loss of muscular strength, no study investigated the benefit of an ERAS concept on skeletal muscles surrounding the hip in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Komiyama et al [ 19 ] recommended cup placement at the anatomic hip center, as the high decreased range of motion in THA leading to the dislocation. Furthermore, Tanaka et al [ 40 ] reported that superior placement of the hip center caused delayed recovery of abductor muscle strength after THA. In the present study, the cup placement in the osteotomy group at an equivalent position to that in the control group was one of the factors that prevented dislocation after THA.…”
Section: Discussionmentioning
confidence: 99%